Passive magnetic coil design for electromagnetic interference evaluation of axle counters - Yoppy, Yoppy; Yudhistira, Yudhistira; Nugroho, Hutomo Wahyu; Trivida, Elvina; Wahyu Wijanarko, Tyas Ari; Bakti, Aditia Nur; Mandaris, Dwi (Institute of Advanced Engineering and Science, 2024)
Measurement of magnetic fields near the railway tracks is crucial to ensure compatibility with the operation of axle counters. According to EN 50592 standard, the magnetic field is detected with a passive magnetic coil and an oscilloscope. From previous studies, in general, there has been no in-depth analysis of how the choice of coil winding parameters could affect the coil output voltage, which then affect the measurement sensitivity, in particular the coil design based on the standard and it is applicability for electromagnetic interference (EMI) evaluation of axle counters. Therefore, this paper will explore the design of a passive magnetic coil to obtain the optimum coil output voltage within the frequency range. Simulations showed that for 10-100 kHz and 100 kHz–1.3 MHz range, the optimum number of turns happened at 60-100 and 15-60 turns, respectively. Based on that, two example coils had been built. Simulations and measurements of their frequency response were in good agreement, with a deviation less than 1.0 dB.